2011
DOI: 10.1016/j.jpeds.2011.03.049
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Surveillance and Detection of Postprandial Hypoglycemia after Fundoplasty in Children

Abstract: Objective To evaluate the prevalence of postprandial hypoglycemia (PPH) after fundoplasty after the initiation of a universal postoperative glucose surveillance plan in the neonatal intensive care unit (NICU). Study design This was a retrospective chart review of children (newborn to 18 years) who underwent fundoplasty at The Children’s Hospital of Philadelphia during the 2-year-period after the launch of a surveillance protocol in the NICU and other units. The rate of screening, frequency of PPH (postprandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 16 publications
(21 reference statements)
1
27
0
Order By: Relevance
“…The dumping syndrome is often quoted, as mentioned previously, to be a major drawback of RYGB surgery (30,32). In our unit, we have shown that most patients, including adolescents, do not experience any symptoms of dumping after RYGB (31), although the prevalence has been reported elsewhere at over 75% (105).…”
Section: Exceptional Circumstancessupporting
confidence: 58%
See 1 more Smart Citation
“…The dumping syndrome is often quoted, as mentioned previously, to be a major drawback of RYGB surgery (30,32). In our unit, we have shown that most patients, including adolescents, do not experience any symptoms of dumping after RYGB (31), although the prevalence has been reported elsewhere at over 75% (105).…”
Section: Exceptional Circumstancessupporting
confidence: 58%
“…The dumping syndrome is divided into early dumping, with gastrointestinal symptoms, and late dumping, typically occurring 1-3 h after a meal without gastrointestinal symptoms (30). Dumping has been reported in adolescents after 32).…”
Section: Introductionmentioning
confidence: 99%
“…Postprandial hypoglycemia is often preceded by exaggerated glucose, glucagon-like peptide-1, and insulin responses, which can be detected on an oral glucose or mixed-meal tolerance test. 35 Values Failure to investigate a neonate, infant, or child with suspected hypoglycemia increases the risk of delaying a definitive diagnosis and instituting effective treatment. Expeditiously identifying the specific cause of hypoglycemia, as outlined above, will enable prompt institution of appropriate treatment and decrease the risk of permanent brain injury from persistent and recurrent severe hypoglycemia.…”
Section: Section 2 Workup/investigation Of Persistent Hypoglycemiamentioning
confidence: 99%
“…Syndromal hyperinsulinism is rare and may be associated with Kabuki, Beckwith-Wiedemann, Soto, Usher, and Turner Syndrome. Finally, miscellaneous forms of hyperinsulinism occur in insulinoma, glucose dumping associated with gastrointestinal surgery such as Nissen fundoplication and post bariatric surgery in adults [8]. …”
Section: Introductionmentioning
confidence: 99%